Plasma cystatin C is a marker of renal glomerular injury in children treated with cisplatin or ifosfamide. Issue 1 (15th October 2020) - Lambert, Marie; White‐Koning, Melanie; Alonso, Mathieu; Garnier, Arnaud; Alphonsa, Gwennaelle; Puiseux, Chloé; Munzer, Caroline; Berthier, Joseph; Malard, Laurence; Pasquet, Marlène; Chatelut, Etienne
Abstract: Background: Plasma cystatin C is a potential marker of the glomerular filtration rate (GFR), and urinary cystatin C has been proposed as a marker of tubular dysfunction. Procedure: A prospective study (NCT02822404) was conducted to assess the benefit of considering cystatin C plasma and urinary levels to better evaluate cisplatin and/or ifosfamide renal toxicity in children with cancer. Plasma 51 Cr‐EDTA clearance as a marker of GFR and urinary markers of tubular toxicity were monitored in 40 children treated by cisplatin and/or ifosfamide. Several equations previously proposed to estimate GFR, with or without inclusion of plasma cystatin C level, were compared. A population pharmacokinetic approach was also used to analyze plasma 51 Cr‐EDTA data, and evaluate the relationship between patient covariates (including plasma cystatin C level) and GFR during the course of chemotherapy treatment. Results: Equations including plasma cystatin C described GFR changes during chemotherapy better than those without this variable. An equation based on plasma cystatin C, serum creatinine, and body weight enabled us to accurately describe the evolution of GFR during chemotherapy. The urinary cystatin C/creatinine ratio was compared between children with or without tubular toxicity, according to a standard assessment of tubular dysfunction. However, although the urinary cystatin C/creatinine ratio was increased in children with tubular toxicity, this marker does not provide additional information to the well‐known markers of tubulopathy. Conclusions: Monitoring of plasma cystatin C may be substituted to radionucleide glomerular exploration in children treated by cisplatin and/or ifosfamide.